THE COMPOSITION OF BIOCOMPOSITE [POLYMETHYLMETHACRYLATE/HYDROXYAPATITE] AS MATERIAL FOR SPECIMEN WITH PORTABEE KIT MACHINE - Kartinasari Ayuhikmatin Sekarjati; Alva Edy Tontowi (SINERGI, 2018)
The development of science and technology related to bone implant material, researchers want to develop materials that have properties near human bones and improve the quality. This study was conducted to determine the composition of the mixture that can pass nozzle at room temperature. It is expected that in this study, the mixture is able to pass through the small nozzle size so that it can print specimens precisely according to the size of the design to be printed. Output mixture through a nozzle is said well if the output is continuous and homogeneous. The quality of the composition of the mixture, the material output from the nozzle will be printed by ASTM F451-95 and compressive test. This mixture consists of polymethylmethacrylate (PMMA), methylmethacrylate (MMA) and hydroxyapatite (HA) by mixing methods manually. PMMA and MMA used in the type of heat curing, while HA derived from fish scales. Through several experiments, there is composition that can pass nozzle and have a high compressive strength value, that is composition PMMA : MMA instead of 1 : 1 (w/w) with mixture 20% HA and have compressive strength value 31,20 MPa, the second composition PMMA : MMA instead of 2 : 1 (w/v) with mixture 10% HA and have compressive strength value 25,62 MPa. This composition was chosen for further research with the Portabee Kit machine.